The Role of Nahdlatul Ulama (NU) in Maintaining Religious Tolerance in Papua: Some ‎Observations - Ridwan Ridwan (Journal of Nahdlatul Ulama Studies, 2020)
The presence of the Transnational Islamic Movement in Papua in the 1998 Reformation era has transformed the relationship between Muslims and Christians which had been harmoniously tense and could even lead to inter-religious conflict. One of the Islamic organisations in Papua working to maintain religious harmony is Nahdlatul Ulama (NU). Therefore, this paper aims to review how the NU responded to the Tolikara incident and the Koya Barat incident. Both cases related to the presence of the transnational Islamic actors in Papua, including Salafi-Wahhabi group, specifically Jafar Umar Thalib’s faction in Papua, which has disturbed interreligious relations. This article argues that Nahdlatul Ulama (NU) plays a vital role in maintaining religious harmony that is in jeopardy with the presence of the transnational Islamic movement in Papua. This paper is based on data from fieldwork that the author has done from the end of 2015 to the early 2019 and is equipped with related library data.